Association of infection, blood transfusion and other clinical factors with retinopathy of prematurity (ROP) (Northern International Medical College Journal, 2015)
Background : In Bangladesh advancement of neonatal care has increased the survival of preterm very low birth weight (VLBW) neonates; thus the incidence of Retinopathy of prematurity (ROP) has also been increased.Objective : To identify the cases of ROP and to observe the association of birth weight, infection and other clinical factors (recorded during hospital stay) with its occurrence.Method : This was a prospective observational study at special care baby unit (SCABU) and Intensive care unit of Dhaka Shishu Hospital from July, 2006 to March, 2008 among premature ( 34 weeks) and/or VLBW ( 1500 gm) neonates. Neonates who fulfilled the inclusion criteria were followed up daily to record certain clinical factors and features suggestive of sepsis.Infants were divided into No ROP group that included newborns without ROP (n=35), and ROP group that included newborns with ROP (n=23). Comparative analysis of recorded clinical factors was done between the two groups.Result : Among the study neonates rate of ROP occurrence is 40% (23 of 58). VLBW, culture proven septicaemia, mean total hours of oxygen inhalation, mechanical ventilation, cumulative volume of blood transfusion, and intra ventricular hemorrhage (IVH) grade II were significantly related with ROP. Stepwise logistic regression analysis revealed birth weight [p=.004, Odds Ratio (OR), .33; Confidence Interval (CI), 0.14 to.436], culture proven septicaemia (p=.005; OR, 4.0 CI, 2.50 to 9.99) and cumulative volume of blood transfusion (p=.013; OR,.43; CI, .028 to .653) to be most significant factors.Conclusion : Rate of ROP occurrence in the current study is 40% and VLBW, culture proven septicaemia and large volume of blood transfusion are significant risk factorsNorthern International Medical College Journal Vol.5(2) 2014: 325-328